Comprensión lectora en sexto grado de primaria de dos instituciones (estatal y privada) de un distrito con alto índice de pobreza: Callao - Sánchez Mancilla, Aurora Elena (2012)
This research is non-experimental and aimed to represent and compare levels of reading comprehension of sixth grade students of two elementary schools (state and private) in a district with high poverty such as Carmen de the League Reynoso – Callao. We used a comparative descriptive design for a sample consisting of 91 sixth grade students: 64 students of the educational institution of the state and 27 private institutions. The instrument applied was ACL6 reading comprehension test (Catala, G., Molina, E., Catala, M. & Monclús, R. (2001) adapted by (Ortega & Ramirez, 2009). Results indicated that there are differences significant in favor of the state educational institution in global reading comprehension and inferential reorganizacional dimensions.